An Analysis of Euphemism in Crimes and Politics News of Posmetro Padang - Yohana Serli; Hamzah Hamzah; Delvi Wahyuni (English Language and Literature, 2018)
This research describes about types and functions of euphemism found in crimes and politics news of Posmetro padang newspaper. The source of data is crimes and politics news during Ramadan, May 16-June 13 2018. From the analysis, in the crimes news there are 9 types of euphemism, namely: metaphor (51), hyperbole (3), circumlocution (6), acronym (22), abbreviation (20), omission (3), synecdoche (2), idiom (12), and metonymy (7). Whereas, in political news uses 6 types of euphemism, namely: metaphor (29), circumlocution (6), acronym (8), abbreviation (8), idiom (12), and litotes (7). Crimes news uses 141 euphemisms and politics news uses 70 euphemisms. Furthermore, there are 2 functions of euphemism in crimes news, they are: concealing (122) and veiling (17). Then, 1 function of euphemism in politics news, concealing (70). So, the most dominant type of euphemism in crimes news and politics news is metaphor, and the most dominant function of euphemism in crimes and politics news is concealing.